PENERAPAN SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL PERSEDIAAN OBAT-OBATAN PADA UPTD PUSKESMAS CIWARINGIN - Yenni Rohmatun; Jenia Dwi Adani (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2022)
This study was to determine the application of accounting information systems and internal control of drug supplies at the Uptd of Ciwaringin Public Health Center. The type of qualitative research is interview and documentation method. The results showed that the application of an accounting information system for drug supplies at the Regional Technical Implementation Unit of the Ciwaringin Health Center was running quite well, the management of drug supplies was carried out manually and computerized, equipped with reports and supporting documents. However, the recording activities on the warehouse card, SMILE, and stock taking are carried out by the same officer. This can lead to the risk of fraud and errors in recording. Meanwhile, the implementation of internal control over the supply of medicines at the Regional Technical Implementation Unit of the Ciwarngin Public Health Center was running quite well and complied with the components of the internal control system. However, in the inventory control activity component, the segregation of duties has not been implemented properly, so there are multiple tasks. Then, the risk assessment component has been done well in dealing with damaged or expired drugs, but officers are still having difficulties in recording